UNIVERSITY STUDENTS’ ASSESSMENT OF GENERAL ENGLISH SUBJECT - Paryati; Nur Affini, Laily (Jurnal Ilmiah Spectral, 2021)
This study analyzed students’ final test in English for General subject, including the students’ overall scores, understanding the essay instruction, and grammar mistakes found in their essay. This research was conducted using a qualitativedescriptive method. The researchers employed document analysis to find related information from the research objectives naturally. The instrument used for the data collection was the students’ answer sheets from the final test, and a summative test was employed as the approach. There were fifty students of non- English Department Study Programs as the participants. The scores achieved conclude that the mean score achieved by the students is in the lowest category. It implies that they still need to improve their writing, such as sentence arrangement, grammar, and vocabulary selection. Furthermore, most students were mistaken in understanding the essay instruction and resulted in incorrect essays.